The association between long‐term PM2.5 exposure and late‐life amyloid burden in the Atherosclerosis Risk in Communities (ARIC) study cohort. (20th December 2022) - Bennett, Erin E; Xu, Xiaohui; Lynch, Katie M; Park, Eun Sug; Ying, Qi; Smith, Richard L; Stewart, James D; Whitsel, Eric A; Mosley, Thomas H; Yanosky, Jeff D; Wong, Dean F; Liao, Duanping; et al.
Abstract: Background: A number of studies show an association between long‐term exposure to ambient particulate matter ≤ 2.5 um (PM2.5 ) and late‐life cognitive impairment. Mechanistic models suggest that PM2.5 may influence cognitive health through promotion of Alzheimer's disease, which is characterized by brain amyloid accumulation. However, the association between long‐term PM2.5 exposure and brain amyloid deposition remains poorly characterized in epidemiological studies. Method: We used data from the Atherosclerosis Risk in Communities (ARIC) study cohort. We used a chemical transport model with data fusion to estimate mean PM2.5 concentrations (ug/m 3 ) in 36‐, 12‐, 4‐, and 1‐km grid cells in ARIC study areas. We linked the concentrations to geocoded participant addresses and calculated mean PM2.5 concentrations from 2000 to 2007. We estimated amyloid deposition using florbetapir amyloid positron emission tomography (PET) scans in 346 ARIC‐PET participants with normal cognition or mild cognitive impairment in 2011‐2014. We defined amyloid positivity as a global cortical standardized uptake value ratio (SUVR) ≥ the sample median of 1.2. We used logistic regression models to quantify the association between amyloid positivity and mean 2000‐2007 PM2.5 concentration after adjusting for potential confounders. We additionally explored effect measure modification by APOE e4 allele status and tested whether effect estimates were consistent using alternate PM2.5 exposure methods. Result: After restricting to participants with non‐missing exposure and confounder data and excluding one participant with dementia, the analytic sample included 279 participants. At the time of amyloid‐PET scans, their mean age was 78 years, 56% were female, 42% were Black, and 26% had mild cognitive impairment. After adjusting for age, sex, education, and race‐study center, we found no significant association between brain amyloid positivity and long‐term mean PM2.5 exposure. We also found no evidence of effect measure modification by APOE e4 allele status. Results were consistent when we used alternate PM2.5 estimation methods. Conclusion: Our findings suggest that ambient PM2.5 may induce neurotoxic effects through non‐amyloid, potentially vascular pathways, though we note the small sample size may have made us underpowered to detect a significant association.